Urinary extracellular vesicles: A position paper by the Urine Task Force of the International Society for Extracellular Vesicles. Issue 7 (21st May 2021) - Erdbrügger, Uta; Blijdorp, Charles J.; Bijnsdorp, Irene V.; Borràs, Francesc E.; Burger, Dylan; Bussolati, Benedetta; Byrd, James Brian; Clayton, Aled; Dear, James W.; Falcón‐Pérez, Juan M.; Grange, Cristina; Hill, Andrew F.; et al.
Abstract: Urine is commonly used for clinical diagnosis and biomedical research. The discovery of extracellular vesicles (EV) in urine opened a new fast‐growing scientific field. In the last decade urinary extracellular vesicles (uEVs) were shown to mirror molecular processes as well as physiological and pathological conditions in kidney, urothelial and prostate tissue. Therefore, several methods to isolate and characterize uEVs have been developed. However, methodological aspects of EV separation and analysis, including normalization of results, need further optimization and standardization to foster scientific advances in uEV research and a subsequent successful translation into clinical practice. This position paper is written by the Urine Task Force of the Rigor and Standardization Subcommittee of ISEV consisting of nephrologists, urologists, cardiologists and biologists with active experience in uEV research. Our aim is to present the state of the art and identify challenges and gaps in current uEV‐based analyses for clinical applications. Finally, recommendations for improved rigor, reproducibility and interoperability in uEV research are provided in order to facilitate advances in the field.